2021
DOI: 10.3390/educsci11110695
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Primary School Teachers’ Intention to Use E-Learning Tools during the COVID-19 Pandemic

Abstract: It is commonly accepted that the COVID-19 pandemic has had a crucial effect on many aspects of people’s lives. The limitations placed on human relations have also affected education. The mandatory implementation of e-learning and the use of the information and communication technology tools in the teaching process have been the most important changes at all educational levels. However, the teaching staff plays a key role in every educational change. In this study, we examined the intention of elementary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…Cohen and Ball (2006) believe that lack of motivation explains the lack of teachers' interest in the adoption and implementation of new technologies in the educational process. Michalakelis and Aivazidi (2021) concluded that the teachers' exhaustion and the resistance to innovation due to the stress caused by the "change" become barriers for the adoption of any innovation in education. Aivazidi and Michalakelis (2021) observed that the mandatory implementation of ICT does not lead to a high-level ICT adoption.…”
Section: Discussion-synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Cohen and Ball (2006) believe that lack of motivation explains the lack of teachers' interest in the adoption and implementation of new technologies in the educational process. Michalakelis and Aivazidi (2021) concluded that the teachers' exhaustion and the resistance to innovation due to the stress caused by the "change" become barriers for the adoption of any innovation in education. Aivazidi and Michalakelis (2021) observed that the mandatory implementation of ICT does not lead to a high-level ICT adoption.…”
Section: Discussion-synthesismentioning
confidence: 99%
“…Michalakelis and Aivazidi (2021) concluded that the teachers' exhaustion and the resistance to innovation due to the stress caused by the "change" become barriers for the adoption of any innovation in education. Aivazidi and Michalakelis (2021) observed that the mandatory implementation of ICT does not lead to a high-level ICT adoption. Moreover, Jimmoyannis and Komis (2007) mentions that teachers are not convinced that ICT solely have a positive impact on the educational process and they believe that the extensive use of ICT can decrease students' social interaction.…”
Section: Discussion-synthesismentioning
confidence: 99%
See 3 more Smart Citations